The role of insulin growth factors in autoimmune diseases - Skarlis, Charalampos; Nezos, Adrianos; Mavragani, Clio P.; Koutsilieris, Michael (Annals of Research Hospitals, 2019)
Insulin-like growth factors (IGFs), their receptors and their binding proteins form a distinct bioregulation system that regulates growth, cell proliferation, apoptosis and tissue remodeling. Recent data highlight a significant interaction of IGFs and the components of the immune system, especially B and T cells. Accumulating data suggest an important role of IGFs in autoimmune diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc) and Sjogren’s syndrome (SS). Herein, we summarize the current evidence on the role of IGF pathway in immune system regulation as well as its potential involvement in the pathophysiology of systemic autoimmune diseases.